Bivalent 14‐mer peptide ligands of CXCR4 with polyproline linkers with anti‐chemotactic activity against Jurkat cells. (12th January 2017) - Tanaka, Tomohiro; Aoki, Toru; Nomura, Wataru; Tamamura, Hirokazu
Abstract : Interaction of CXCR4 with its endogenous ligand, stromal‐cell derived factor‐1 (SDF‐1)/CXCL12, induces various physiological functions involving chemotaxis. Bivalent ligands with a polyproline helix bearing a cyclic pentapeptide, FC131, were previously shown to have higher binding affinities for CXCR4 than the corresponding monovalent ligands. Bivalent ligands based on a 14‐mer peptide T140 derivative with polyproline linkers have been designed and synthesized. The activity of these peptides as well as the effect of bivalency of the ligand on CXCR4 binding has been assessed. The binding affinity of these series of bivalent ligands is increased as the linker length increases up to the 12‐/15‐mer proline linker. The inhibitory activity against chemotaxis on Jurkat cells also depends on the linker length. The T140‐derived bivalent ligands with the 9‐ and 12‐mer proline linkers showed the most effective inhibition against chemotaxis at 1000 nM, which is even higher than that of known CXCR4 antagonists in the monomer structure. The effective metastatic inhibition by bivalent T140 derivatives indicates the therapeutic potential. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Bivalent ligands based on a 14‐mer peptide T140 derivative with polyproline linkers have been synthesized. The activity of these peptides as well as the effect of bivalency of the ligand on CXCR4 binding has been assessed. The binding affinity of these series of bivalent ligands is increased as the linker length increases up to the 12‐/15‐mer proline linker. The T140‐derived bivalent ligands with the 9‐ and 12‐mer proline linkers showed the most effective inhibition against chemotaxis at 1000 nM, which is even higher than that of known CXCR4 antagonists in the monomer structure.